Ulam stability of hom-ders in fuzzy Banach algebras - Araya Kheawborisut; Siriluk Paokanta; Jedsada Senasukh; Choonkil Park (My University, 2022)
This paper aims to investigate a new type of derivations in a fuzzy Banach algebra. Moreover, by using the fixed point method, we obtain some stability results of the hom-der in fuzzy Banach algebras associated with the functional equation \begin{document}$ f(x+{\textbf{k}}y) = f(x)+{\textbf{k}}f(y) $\end{document} where $ {\textbf{k}} $ is a fixed positive integer greater than $ 1 $.
Keywords: Banach algebra; Functional Equations Stability Results